2019
DOI: 10.1007/s13197-019-03685-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ripening on the in vitro antioxidant capacity and bioaccessibility of mango cv. ‘Ataulfo’ phenolics

Abstract: Fruit ripening induces changes that strongly affect their matrices, and consequently, the bioaccessibility/bioavailability of its phenolic compounds. Flesh from 'slightly' (SR), 'moderately' (MR) and 'fully' (FR) ripe 'Ataulfo' mangoes were physicochemically characterized, and digested in vitro to evaluate how ripening impacts the bioaccessibility/bioavailability of its phenolic compounds. Ripening increased the flesh's pH and total soluble solids, while decreasing citric acid, malic acid and titratable acidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…To date, there are two reports describing the in vitro bioaccessibility of mango polyphenols in ‘Ataulfo’ by-products from pulp paste and peel [ 18 ] and in mangoes with different ripening stages [ 19 ]. More recently, another two studies have shown the importance of colonic microbiota in the metabolism of mango polyphenols by evaluating the bioaccessibility and colonic fermentation of high-dietary fiber mango-based fruit bars [ 20 ] or mango bagasse formulations [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are two reports describing the in vitro bioaccessibility of mango polyphenols in ‘Ataulfo’ by-products from pulp paste and peel [ 18 ] and in mangoes with different ripening stages [ 19 ]. More recently, another two studies have shown the importance of colonic microbiota in the metabolism of mango polyphenols by evaluating the bioaccessibility and colonic fermentation of high-dietary fiber mango-based fruit bars [ 20 ] or mango bagasse formulations [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bioaccessibility of phenolic compounds was related to the chemical structure and stability of phenolic compounds during the digestion process (Dutra et al., 2017). Moreover, the interaction of phenolics with the food matrix could influence the solubility and availability of phenolic compounds (Quirós‐Sauceda et al., 2019). Alkaline and enzymatic hydrolysis can release phenolic compounds from the food matrix under GI conditions, which can improve the bioaccessibility and bioavailability of phenolic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Mango pulp is a good source of many micro-and macro-minerals such as calcium, sodium, copper, iron, phosphorus, manganese, magnesium, zinc, boron (0.6-10.6 mg/kg), and selenium. The pulp is also rich in organic acids including citric acid, malic acid, oxalic acid, succinic acid, ascorbic acid, and tartaric acid, and bioactive compounds such as phenolic acids, sterols, and alkaloids [27,28].…”
Section: Pulpmentioning
confidence: 99%